2019
DOI: 10.1108/jcrpp-04-2019-0026
|View full text |Cite
|
Sign up to set email alerts
|

What works in fraud prevention: a review of real-world intervention projects

Abstract: Purpose The purpose of this paper is to report on a search of criminology and related databases to identify fraud prevention intervention projects that showed promising achievements in reducing offences. Design/methodology/approach A keyword search of Criminal Justice Abstracts was supplemented by searches of related databases and cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Those studies have been found in year 1998, 2003, 2012, 2015, 2017, 2018, 2019, 2020 and 2021 and the studies have been discovered through bibliometric search. Prevention and detection mechanisms such as internal control, data mining technology used to detect financial fraud and extensive knowledge and practice in Explain the Audit Procedure (EDP) as a part of fraud detection are all found to be the measures used to combat fraud (Abd Karim et al, 2018;Madi et al, 2021;Dangi et al, 2020;Zakaria et al, 2016;Azmi and Ismail, 2022;Alam et al, 2018;Muhamad and Gani, 2020;Ali et al, 2021;Musa et al, 2012;Aziz et al, 2021;Vanasco, 1998;Mwelu and Watundu, 2020;Quah, 2015;Alazzabi and Karage, 2020;Prenzler, 2019;Abramo and Brasil, 2003;Howell, 2017;Šnjegota, 2017;Iskandar, 2019;Al-Hashedi and Magalingam, 2021;Donning et al, 2019;Nawawi and Salin, 2018). Those researches were from the journal of financial crime, International Journal of Law and Management, Journal of Financial Reporting and Accounting, International Journal of Ethics and Systems, Journal of Finance and Risk Perspectives and Journal of Criminological Research, Policy and Practice.…”
Section: Fraud Prevention and Detection Mechanismsmentioning
confidence: 99%
“…Those studies have been found in year 1998, 2003, 2012, 2015, 2017, 2018, 2019, 2020 and 2021 and the studies have been discovered through bibliometric search. Prevention and detection mechanisms such as internal control, data mining technology used to detect financial fraud and extensive knowledge and practice in Explain the Audit Procedure (EDP) as a part of fraud detection are all found to be the measures used to combat fraud (Abd Karim et al, 2018;Madi et al, 2021;Dangi et al, 2020;Zakaria et al, 2016;Azmi and Ismail, 2022;Alam et al, 2018;Muhamad and Gani, 2020;Ali et al, 2021;Musa et al, 2012;Aziz et al, 2021;Vanasco, 1998;Mwelu and Watundu, 2020;Quah, 2015;Alazzabi and Karage, 2020;Prenzler, 2019;Abramo and Brasil, 2003;Howell, 2017;Šnjegota, 2017;Iskandar, 2019;Al-Hashedi and Magalingam, 2021;Donning et al, 2019;Nawawi and Salin, 2018). Those researches were from the journal of financial crime, International Journal of Law and Management, Journal of Financial Reporting and Accounting, International Journal of Ethics and Systems, Journal of Finance and Risk Perspectives and Journal of Criminological Research, Policy and Practice.…”
Section: Fraud Prevention and Detection Mechanismsmentioning
confidence: 99%
“…Considering the literature review and in accordance with Prenzler (2020), the following question arises to address the second research objective: Could the methods and techniques used by forensic auditors be implemented as deterrents to prevent financial statement fraud?…”
Section: Jfc 303mentioning
confidence: 99%
“…In general, the literature is marked by inferences about what should work, which are based on diagnoses of fraud opportunity factors and victim characteristics. However, there is an urgent need for scientific studies of effective anti-fraud interventions (Prenzler, 2020), not only against occupational or internal fraud (which is executed by an employee for personal benefit) but also against financial statement fraud, which is usually prepared by corporate executives whose compensation is closely tied to employer financial performance (Buckhoff et al , 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, the DOD Inspector General (DOD IG) has highlighted DOD contract management as a “Top 10 Management Challenge for 2020” due to its defense acquisition contracts being a high risk for fraud (DODIG, 2019). As the DOD continues to increase its procurement of defense logistics support services, so have the occurrences of procurement fraud increased (Prenzler, 2019). The DOD IG has reported that:…”
Section: Introductionmentioning
confidence: 99%